The role of land deed officials or Pejabat Pembuat Akta Tanah (PPAT) in preventing agricultural land ownership exceeding the maximum area limit - Faizal Achmad; Chandra Maharani; Agus Agus; Elvita Rossyana; Tamara Mutiara (Priviet Social Sciences Journal, 2026)
This study analyzes the effectiveness of land deed officials or Pejabat Pembuat Akta Tanah (PPAT) in preventing agricultural land ownership from exceeding the maximum limit under national agrarian regulations, which still faces obstacles regarding ownership inequality and weak control over land rights transactions. The main problem lies in the ineffective legal instruments and the lack of supervision over the transfer of land rights, which can potentially lead to excessive land ownership by a few individuals. Using an empirical juridical approach, this study combines a normative analysis of laws and regulations with in-depth interviews with PPATs/Notaries in the Kubu Raya Regency. This study collected primary data from informants and secondary data from legal literature and regulatory documents. The results show that PPATs play a strategic role in ensuring compliance with the principle of legality and land ownership limits. However, their effectiveness is still limited by regulatory constraints, the lack of an integrated national land ownership database, and poor coordination among government agencies. The study concludes that strengthening the legal framework, increasing supervision, and integrating land data are crucial steps to support fair land governance and accelerate agrarian reforms. These points also serve as the main recommendations for future studies.